Biological effect of LOXL1 coding variants associated with pseudoexfoliation syndrome. (May 2016) - Sharma, Shiwani; Martin, Sarah; Sykes, Matthew J.; Dave, Alpana; Hewitt, Alex W.; Burdon, Kathryn P.; Ronci, Maurizio; Voelcker, Nicolas H.; Craig, Jamie E.
Abstract: Pseudoexfoliation (PEX) syndrome is a systemic disease involving the extracellular matrix. It increases the risk of glaucoma, an irreversible cause of blindness, and susceptibility to heart disease, stroke and hearing loss. Single nucleotide polymorphisms (SNPs) in the LOXL1 ( Lysyl oxidase-like 1 ) gene are the major known genetic risk factor for PEX syndrome. Two coding SNPs, rs1048861 (G > T; Arg141Leu) and rs3825942 (G > A; Gly153Asp), in the LOXL1 gene are strongly associated with the disease risk in multiple populations worldwide. In the present study, we investigated functional effects of these SNPs on the LOXL1 protein. We show through molecular modelling that positions 141 and 153 are likely surface residues and hence possible recognition sites for protein–protein interactions; the Arg141Leu and Gly153Asp substitutions cause charge changes that would lead to local differences in protein electrostatic potential and in turn the potential to modify protein–protein interactions. In RFL-6 rat fetal lung fibroblast cells ectopically expressing the LOXL1 protein variants related to PEX (Arg141_Gly153, Arg141_Asp153 or Leu141_Gly153), immunoprecipitation of the secreted variants showed differences in their processing by endogenous proteins, possibly Bone morphogenetic protein-1 (BMP-1) that cleaves and leads to enzymatic activation of LOXL1. Immunofluorescence labelling of the ectopically expressed protein variants in RFL-6 cells showed no significant difference in their extracellular accumulation tendency. In conclusion, this is the first report of a biological effect of the coding SNPs in the LOXL1 gene associated with PEX syndrome, on the LOXL1 protein. The findings indicate that the disease associated coding variants themselves may be involved in the manifestation of PEX syndrome. Highlights: PEX syndrome associated LOXL1 coding variants likely encode surface residues. PEX associated LOXL1 protein variants exhibit differential extracellular processing. PEX associated LOXL1 protein variants exhibit similar accumulation propensity. PEX syndrome associated LOXL1 coding variants may directly contribute to the disease.